2019 41st Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2019
DOI: 10.1109/embc.2019.8856745
|View full text |Cite
|
Sign up to set email alerts
|

Differential Diagnosis for Pancreatic Cysts in CT Scans Using Densely-Connected Convolutional Networks

Abstract: The lethal nature of pancreatic ductal adenocarcinoma (PDAC) calls for early differential diagnosis of pancreatic cysts, which are identified in up to 16% of normal subjects, and some of which may develop into PDAC. Previous computer-aided developments have achieved certain accuracy for classification on segmented cystic lesions in CT. However, pancreatic cysts have a large variation in size and shape, and the precise segmentation of them remains rather challenging, which restricts the computer-aided interpret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 13 publications
0
12
0
2
Order By: Relevance
“…Additionally, saliency maps were generated to highlight the important pixels within the image and to visualize the critical areas that contributed to the classification output. The DL model achieved an accuracy of 73%, while the accuracy of the radiologists in this cohort was 48% 28 . Surprisingly, the saliency maps showed that critical information was derived not only from the region around the PCN, but also from the boundaries of the pancreas, indicating that the shape of the pancreas border contributes to the eventual decision.…”
Section: Cystic Lesions Of the Pancreasmentioning
confidence: 76%
See 3 more Smart Citations
“…Additionally, saliency maps were generated to highlight the important pixels within the image and to visualize the critical areas that contributed to the classification output. The DL model achieved an accuracy of 73%, while the accuracy of the radiologists in this cohort was 48% 28 . Surprisingly, the saliency maps showed that critical information was derived not only from the region around the PCN, but also from the boundaries of the pancreas, indicating that the shape of the pancreas border contributes to the eventual decision.…”
Section: Cystic Lesions Of the Pancreasmentioning
confidence: 76%
“…The DL model achieved an accuracy of 73%, while the accuracy of the radiologists in this cohort was 48%. 28 Surprisingly, the saliency maps showed that critical information was derived not only from the region around the PCN, but also from the boundaries of the pancreas, indicating that the shape of the pancreas border contributes to the eventual decision. Wei et al developed a ML-based model to differentiate between SCNs and non-SCNs based on radiomic features from preoperative CT images.…”
Section: Cystic Lesions Of the Pancreasmentioning
confidence: 94%
See 2 more Smart Citations
“…In addition to pancreatic cancer a number of groups have explored the application of AI for the identification of pancreatic cystic masses using traditional machine learning and demonstrated that it was possible to achieve average accuracies and AUC of 66% to 93% and 0.75 to 0.837. [37][38][39][40][41] Deep learning methods such as CNN have also been employed for PDAC detection and diagnosis. Liu et al [42] employed a faster region-based CNN and analysed more than 6000 CT images from 338 PDAC patients.…”
Section: The Application Of Ai In the Diagnosis Of Pancreatic Cancermentioning
confidence: 99%